ANALYSIS OF COMMERCIAL CUSTOMER SATISFACTION LEVEL IN PT PERUSAHAAN GAS NEGARA (PERSERO) TBK SBU DISTRIBUSI WILAYAH III SUMATERA BAGIAN UTARA - Firman Ario (International Journal of Economic, Technology and Social Sciences (Injects), 2021)
This study examined of Commercial Customer Satisfaction Level In PT Perussahaan Gas Negara (Persero) Tbk, SBU Distribusi Wilayah III Sumatera Bagian Utara. . The study used descriptive statistical analysis using cartesian diagram which divided into four parts bounded by two lines that intersect perpendicularly at points X and Y. This diagram is also called the importance-performance matrix is used to describe the priority dimension of service quality. or service attributes that need to be improved and serve as a guide for formulating improvement strategies based on decrease in the number of customers in the commercial customer segment from 579 customers in 2012 to 540 customers in 2017, while customers in other segments, namely industry and households increased. The population in this study is all commercial customers in the State Gas Company (Persero) Tbk SBU Distribusi Region III in Medan City as many as 540 commercial customers during the period of 2018. Sampling technique in this study by using probability sampling method with simple random sampling technique. From the results of the research and discussion described in the previous chapter, it is concluded that based on the Descriptive Analysis and Cartesian Diagram Analysis that the influence of service quality consists of: tangible (direct evidence), reliability (reliability), responsiveness (responsiveness), assurance (guarantee). ), and empathy for the level of satisfaction of commercial customers at PT. Perusahaan Gas Negara (Persero) SBU Distribusi Wilayah III Sumatera Bagian Utara is categorized as sufficient. From the five dimensions of service quality, the most dominant variable inservice improvement is the tangible variable (direct evidence).